The Effect of Tenors, Installments, Loans on Arrears, and Moderating Variables - Ardiansyah (LPPM Universitas Terbuka, 2023)
The research objective is to determine the effect of tenors, installments, and loans on arrears and moderating variables. This type of quantitative research. Secondary data type. The research population for customer loan data for 2017-2022 and customer loans maturing in 2022-2027 are 527 customers as a sample. The analytical method uses path analysis with the help of SmartPLS 3. The results of the study: (1) Tenors have a negative and significant effect on Arrears; (2) Tenors have a negative and significant effect on Installment; (3) Loans have a positive and significant effect on Tenors; (4) Loans have a positive and significant effect on Arrears; (5) Loan has a positive and significant effect on Installment; (6) Installment has a negative and significant effect on Arrears; (7) Loans are not significant to Arrears moderated by Installment; and (8) Tenors have a negative and significant effect on Arrears moderated by Installment. The research findings provide empirical evidence that the determinants of customer arrears that can have an impact on arrears are tenors, loans, and installments. The implication of the research results is the discovery of factors that need to be considered by the company in providing loans to customers by carefully considering the alignment between loans to tenors, then tenors to installments so that the determination is not burdensome to customers so that arrears are smaller and can increase company profitability. Recommendations for further research: (1) Conduct data analysis on consumptive and productive loans; (2) Develop variables: Remaining loan principal, Arrears of fines, and Interest arrears.